Anthony Bourdain, no reservations. Collection 3 [videorecording (DVD)] - Bourdain, Anthony (Distributed by Image Entertainment, 2009)
The globe-trotting hedonist known as the 'gastronomic Indiana Jones' scrupulously explores a locale's cuisine like no other TV traveler. In season three, he nibbles caviar, goes clubbing in Moscow, samples Thai noodles in Los Angeles, and so much more.